Evaluation of Thermodynamic Parameters of Conduction Polymer in Solutions Using Ultrasonic Interferrometric Technique - R. Palanivel, K. Balamurugan, N. Shanmugam (Recent Research in Science and Technology, 2009)
The electrical conduction polymer Polyaniline (PANI) base is soluble in selected organic (polar) solvents. The PANI becomes conductive upon partial oxidation or reduction by a process commonly known as doping. The PANI base was doped by chemical method using perchloric acid (HClO4) as a dopant. The doped conducting polymer was dissolved in three selective organic solvents namely p-Cresol (PCL), Dimethyl sulphoxide (DMSO) and 2-Chlorophenol (2CPL). The ultrasonic velocity values were measured for the polymer in solutions using fixed frequency (3MHz) continuous wave ultrasonic interferometer technique at three different temperatures. The related thermodynamic parameters were calculated and their variations with concentration have been discussed with a view to understand the molecular interactions of the conduction polymers in solutions. Hence the acoustic properties of doped PANI in solutions will provide possibly a new product ideas and benefits over the traditional polymers owing to its properties in solutions.